Peran Komunikasi Interpersonal Karyawan dalam Meningkatkan Kualitas Pelayanan Pelanggan: Studi pada Store RELX Family Mart Thamrin - Hilda Fatmayanti; Meilanta Rantina (Jurnal Pendidikan Transformatif (JPT), 2026)
This study aims to explore how interpersonal communication among employees contributes to improving service quality at the RELX Family Mart store in Thamrin. The research focuses on the importance of quality service amidst today's intense business competition, particularly when consumers require a deeper understanding of available products—ranging from their functions and variant options to usage instructions. A qualitative descriptive approach utilizing a case study strategy was employed. Data collection involved face-to-face interviews with informants, field observations, and the gathering of supporting documents. The findings indicate that interactions between employees and customers foster a positive atmosphere, characterized by employees providing detailed and easily understandable product explanations. This underscores that interpersonal communication is a crucial, indispensable factor in delivering satisfying service.